Infraestruturas virtuais de computação científica aplicadas na mitigação de heterogeneidade semântica de dados ambientais - Rodrigues, Rodicrisller (2015)
With the diffusion of electronic devices and the facility in exchange of information any scientific project uses data from different sources. In this context, scientific data have semantic aspects inherent to the process of acquisition and domain area, in such a way to work with different sources of data sets is necessary to solve the problem of semantic heterogeneity between them. This work focuses on the mitigation of the heterogeneity on scientific data using virtual infrastructures for Scientific Computing. The main objective is to demonstrate that computational cloud solutions have the necessary requirements to meet the current demands of the context of Scientific Computing and e-Science, in order to facilitate the exchange and interaction of data between heterogeneous environments.